الدعوة الإسلامية في الصين : عوائق وحلول - شاو، تينج مريم سيف الله (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The study aims at highlighting the realities of Islamic Da'wah in China and looking at obstacles encountered by Da'wah activists in the country. It also aims at proposing possible ways to overcome these obstacles. The descriptive, analytical and comparative methods have been adopted by the researcher to build a body of knowledge and information on the subject matter which includes the history of the arrival and spread of Islam in China and examining crucial issues underneath the political, social, and religious realities that continuously challenge Islamic Da'wah. The study concludes that Islamic Da'wah in China is susceptible to complex challenges that equally require complex and creative ways of dealing with them. Any measure that is taken to face these challenges should take into consideration the present realities of China and they should also be guided by the Divine guidance and Prophetic methodology that accord those realities.